Socio-Ecological Problem Posing in Waste Context: Socio-Ecological Awareness and Mathematical Thinking of Preservice Mathematics Teachers - Tina Rosyana; Tatag Yuli Eko Siswono; Abdul Haris Rosyidi; Sugi Hartono (Universitas Muhammadiyah Malang, 2026)
Socio-ecological issues increasingly require mathematics education to connect mathematical learning with sustainability-related problems encountered in everyday life. In this context, problem posing provides opportunities for students to formulate mathematical problems and to interpret socio-ecological phenomena through mathematical reasoning. This study aims to examine socio-ecological problem posing in waste contexts by investigating the mathematical problems posed by preservice mathematics teachers, the manifestation of socio-ecological awareness reflected in their responses, and their mathematical thinking patterns. This study employed an interpretive qualitative approach involving six sixth-semester preservice mathematics teachers enrolled in a socio-ecological mathematics education course at a teacher education institution in Cimahi, Indonesia. Data were collected through a problem-posing worksheet designed around waste-related issues in Cimahi City and analyzed using qualitative content analysis. The findings reveal that participants generated diverse and contextual mathematical problems related to landfill capacity, waste growth, waste reduction, and community-based waste management. Socio-ecological awareness emerged through ecological awareness, social awareness, socio-ecological interconnectedness, and solution orientation. Furthermore, participants demonstrated variations in mathematical thinking, particularly in identifying quantities, establishing relationships between variables, constructing mathematical representations, and engaging in systematic reasoning. The findings suggest that socio-ecological problem posing may help preservice mathematics teachers connect mathematics with sustainability issues and provide insights into how they interpret socio-ecological problems through mathematical thinking. These findings have practical implications for school mathematics teaching by demonstrating how socio-ecological problem posing can be used to connect mathematical concepts with authentic sustainability issues. Such activities may support students in developing mathematical reasoning, systems thinking, and awareness of environmental challenges through meaningful classroom contexts.